Confocal laser scanning microscopy for rapid optical characterization of graphene. Issue 1 (December 2018) - Panchal, Vishal; Yang, Yanfei; Cheng, Guangjun; Hu, Jiuning; Kruskopf, Mattias; Liu, Chieh-I.; Rigosi, Albert; Melios, Christos; Hight Walker, Angela; Newell, David; Kazakova, Olga; Elmquist, Randolph
Abstract Two-dimensional (2D) materials such as graphene have become the focus of extensive research efforts in condensed matter physics. They provide opportunities for both fundamental research and applications across a wide range of industries. Ideally, characterization of graphene requires non-invasive techniques with single-atomic-layer thickness resolution and nanometer lateral resolution. Moreover, commercial application of graphene requires fast and large-area scanning capability. We demonstrate the optimized balance of image resolution and acquisition time of non-invasive confocal laser scanning microscopy (CLSM), rendering it an indispensable tool for rapid analysis of mass-produced graphene. It is powerful for analysis of 1–5 layers of exfoliated graphene on Si/SiO2, and allows us to distinguish the interfacial layer and 1–3 layers of epitaxial graphene on SiC substrates. Furthermore, CLSM shows excellent correlation with conventional optical microscopy, atomic force microscopy, Kelvin probe force microscopy, conductive atomic force microscopy, scanning electron microscopy and Raman mapping. The development of two-dimensional (2D) layered materials is of particular importance for future electronics applications. The authors show how Confocal Laser Scanning Microscopy outperforms other characterizing techniques for wafer-scale graphene.